2D problem of nonlocal rotating thermoelastic half-space with memory-dependent derivative. Issue 2 (29th March 2022) - Said, Samia M.
Abstract : Purpose: The present study discussed wave propagation in a nonlocal generalized thermoelastic half-space with moving an internal heat source under influence of rotation. Design/methodology/approach: Normal mode analysis is introduced to obtain the analytical expressions of the physical quantities. Findings: Numerical results are presented graphically to explore the effects of rotation, the nonlocal parameter, and the time-delay on the physical quantities. It is found that the physical quantities are affected by rotation, the nonlocal parameter, and the time-delay. Originality/value: The problem is solved based on the classical-coupled theory, the Lord–Shulman theory, and the Green–Lindsay theory with memory-dependent derivative (MDD).